THIRFTING SEBAGAI TREN WISATA URBAN DI KOTA AMBON - Pattiwaellapia, Mareldy S; Tutupary , Victor D.; Pakniany, Yamres (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This research discusses the trend of thrifting, which is much loved by the surrounding community and, more specifically, by teenagers and students when viewed from an urban tourism perspective. This research is in the Mardika Area, Rijali Village, Sirimau District, Ambon City. At this time, thrifting has become one of the places visited by the people of the city of Ambon. People prefer to buy thrifting products because the prices are affordable, and they can get good products. This study used a qualitative research method, with data collection techniques in the form of interviews conducted with several informants, both thrifting buyers and enthusiasts and also thrifting product sellers in the Mardika area. The results of this study indicate that the community needs the development of thrifting buildings and environmental cleanliness. Therefore, thrifting development is carried out using 4A, namely, attraction, accessibility, amenities, and ancillary, as well as a development strategy based on SWOT.